2017
DOI: 10.3126/jsan.v4i1.17445
|View full text |Cite
|
Sign up to set email alerts
|

An audit of hepatobiliary diseases in a tertiary level intensive care unit in Nepal

Abstract: Background: Hepatobiliary diseases account for significant proportion of admission in our intensive care unit, a semi-closed, 11 bedded mixed medical-surgical unit. This study was conducted to study the profile of patients with various hepatobiliary diseases who required intensive care unit admissions with the aim of identifying the need for a hepatobiliary critical care facility. Methods: A retrospective study was designed and all consecutive patients admitted with hepatobiliary problems from January 2013 til… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The use of OTC antibiotics increased during the COVID-19 pandemic for several reasons. The high empirical treatment through prescription from clinicians and OTC-based use of antibiotics echoes studies from Nepal [22][23][24][25][26], Scotland [29], Saudi Arabia [30], Peru [31], and Bangladesh [32]. Indeed, the overuse of antibiotics during the pandemic has been reported globally [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of OTC antibiotics increased during the COVID-19 pandemic for several reasons. The high empirical treatment through prescription from clinicians and OTC-based use of antibiotics echoes studies from Nepal [22][23][24][25][26], Scotland [29], Saudi Arabia [30], Peru [31], and Bangladesh [32]. Indeed, the overuse of antibiotics during the pandemic has been reported globally [11].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from Nepal, found that around 70-98% of COVID patients were treated with antibiotics in the hospital [22][23][24]. Another study found more than half of patients admitted in intensive care unit (ICU) in a tertiary care hospital were prescribed empirical antimicrobials [25]. The use of antibiotics was widespread even when only around half of the COVID infections had bacterial co-infections, and among severe and moderate COVID patients, around 20-25% had antimicrobial resistant bacterial infections [26].…”
Section: Introductionmentioning
confidence: 99%